Conhecimento ecológico e manejo de produtos florestais não-madeireiros por comunidades tradicionais da amazônia - Medeiros, Tássia Karina Alexandre de (Universidade Federal Rural do Semi-Árido, 2018)
Among the products and benefits of the Amazon forest, non-timber forest products (NTFPs) stand out for providing considerable support to local communities in the form of food, medicines, fuel, plants of cultural importance, as well as representing a source of significant income. Currently, the most notable NTFP in this forest is Brazil nut (Bertholletia excelsa), widely recognized as one of the most economically and socially valuable species. In this way, the objectives of this work are to evaluate the sustainability of Brazil nut extraction (Chapter 1) and to make a diagnosis of the scientific knowledge and traditional knowledge about the main non-timber forest products exploited by the extractivists in the Extractive Reserve of Rio Ouro Preto, located in the State of Rondônia (chapter 2). The evaluation of the sustainability of chestnut extractivism was carried out using the MESMIS method (Framework for the Evaluation of Natural Resource Management Systems incorporating Sustainability Indicators). In order to do so, 24 sustainability indicators were created, distributed in the environmental, economic and social dimensions. For data collection, 56 semi-structured interviews with extractivists of the said reserve were carried out, being these 29 collectors of chestnut that live in the aquatic area and 27 in the terrestrial area. The two areas were compared to evaluate potential differences in resource management, which could be important in designing strategies to increase collection sustainability. In general, the management system related to Brazil nut extraction reached intermediate values in terms of sustainability and, from the environmental point of view, no problems were detected that threaten the continuity of the collection. However, in order to reach the ideal values considered sustainable as a whole, changes in the socioeconomic aspects associated with extractivism are needed, as well as the development of public policies for the development of RESEX Rio Ouro Preto, guaranteeing the traditional populations better living conditions within these units. In Chapter 2 we selected species with a history of non-timber use by local communities, as well as indicators of ecological sustainability with the help of specialized literature. The collection of academic data on species and indicators was done through database research, while traditional ecological knowledge was assessed using the focus group technique during participatory workshops. Data analysis was performed using multivariate statistics and demonstrated some convergences between different knowledge systems. Such convergences allowed the identification of species with a potential for sustainable management, among them açaí (Euterpe precatoria), patauá (Oenocarpus bataua), cupuí (Theobroma subincanum), pama miratinga (Pseudolmedia laevis), true rubber tree (Hevea brasiliensis), rubber tree itaúba Hevea guianensis) and buriti (Mauritia flexuosa). In addition, the babaçu (Attalea speciosa) also presented potential for sustainable management in the Rio Ouro Preto RESEX. On the other hand, iron cougarú (Dipteryx odorata), coulorú (Amburana acreana), uxi (Endopleura uchi), gameleira (Ficus maxima) and red toarí (Cariniana micranta) presented no ecological potential for exploration, in the scope of participatory management, in order to generate management systems aiming at sustainability
Keywords: Extrativismo; Castanha-do-Brasil; Indicadores de sustentabilidade; Conservação; Extractivism; Brazil nut; Sustainability indicators; Conservation; CIENCIAS BIOLOGICAS::ECOLOGIA